Early life history timings in marbled rockcod (Notothenia rossii) fingerlings from the South Shetland Islands as revealed by otolith microincrement - Barrera Oro, Esteban; La Mesa, Mario; Moreira, María Eugenia (Polar Biology)
Although it has been reported that Notothenia rossii elsewhere hatches in spring, our daily increment back-counting from the capture date in otoliths of fingerlings caught in Potter Cove, South Shetland Islands, in the 2000s, showed two main periods of larval hatching, one in summer (February–March) and another in winter (July). In concordance, the simultaneous presence of two cohorts born the same year was identified in the age/length frequency distribution of fish sampled in spring 2010, which belonged to biological ages 0+ and 1+ and hatched, respectively, in summer and winter–spring. Maximum and minimum ages of pelagic blue-phase and demersal brown-phase fingerlings were, respectively, 227 and 240 days, indicating a demersal settlement after about 8 months from hatching. The estimated growth rate was 0.23–0.33 mm/day, equivalent to that of South Georgia fingerlings and higher than those of other nototheniids of similar size range. Based on early life events associated with the hatching periods, two types of life cycles are hypothesised for South Shetland fingerlings. The pelagic blue-phase fingerlings (6.5–7.6 cm TL, age group 0+) hatched in July (winter cohort), entering in Potter Cove in February–March. The brown-phase fingerlings (6.3–10.6 cm, mostly of age group 0+) hatched in February–March (summer cohort) and were collected in the cove in spring (the smaller specimens) or in summer (the larger ones). Finally, early juveniles (10.7–15.5 cm, age group 1+) hatched in winter, mainly in July (winter cohort), entering in the cove the following year to spend the second winter inshore. Fil: Barrera Oro, Esteban. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. Dirección Nacional del Antártico. Instituto Antártico Argentino; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina Fil: La Mesa, Mario. Consiglio Nazionale delle Ricerche. Istituto Di Scienze Marine; Italia Fil: Moreira, María Eugenia. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. ...